Voting Against Your Constituents? How Lobbying Affects Representation. Issue 1 (6th May 2015) - Giger, Nathalie; Klüver, Heike
Abstract : Citizens delegate the representation of their political preferences to members of Parliament (MPs), who are supposed to represent their interests in the legislature. However, MPs are exposed to a variety of interest groups seeking to influence their voting behavior. We argue that interest groups influence how MPs cast their vote in Parliament, but that this effect varies across groups. While lobbying by sectional groups provides incentives for MPs to defect from their constituents, we expect that cause groups in fact strengthen the link between MPs and their voters. We test our argument based on an innovative study of 118 Swiss public referenda, which allows for directly comparing voter preferences with legislative voting of 448 MPs on these issues. Drawing on a multilevel regression analysis, this study shows that interest groups considerably affect the link between MPs and their voters. Our findings have important implications for our understanding of political representation.